Isolation of Endophytic Fungi from Adhatoda vasica and Assessing its Antibacterial Efficacy and Cytotoxic Impact on the A549 Cancer Cells - Jenifer Jincy. T; Biji C. P; Chithra, A. Vijaya (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The current study investigated the anti-bacterial and anti-cancer properties of endophytic fungi obtained from medicinal plant Adhatoda vasica. We isolated and identified the endophytic fungi Humicola fuscoatra. by examining their morphological characteristics and microscopic structures. We then extracted their secondary metabolites using ethyl acetate. The ethyl acetate extracts of the fungus H. fuscoatra have shown promising effectiveness against human pathogens, including Klebsiella pneumoniae, Escherichia coli, Bacillus subtilis, and Staphylococcus aureus. A strain of H. fuscoatra exhibited significant antibacterial activity. In addition, we have assessed the effects of ethyl acetate extracts from the fungus H. fuscoatra on the growth of the human lung cancer cell line A549 in vitro assays. Using ethyl acetate extracts from the fungus H. fuscoatra effectively suppressed the growth, survival, migration, and invasion of cancer cells. In this paper we studied in detail the identification of isolated endophytic fungi H. fuscoatra from Adhatoda vasica and characterized its active metabolite compounds. The ethyl acetate-extracted secondary metabolites from the fungal culture supernatant were analyzed using gas chromatography and mass spectrometry, which detected the presence of Hexadecanoic Acid, Hexadecane, Heptadecane, Octadecane, Octadecanoic acid, phytochemicals. The results suggest that the endophytic fungus H. fuscoatra found in medicinal plants has the potential to produce bioactive compounds. They could also be used as a biocontrol agent against bacterial pathogens and for therapeutic purposes in the A549 lung cancer cell line.